Empirical Analysis of Residential Electricity Demand: A Case Study of South Africa - Rangelova,Gergana (2012)
The current study looks at residential electricity consumption trends in a middle income country – South Africa over the period 1978-2010. The country is put in a comparative perspective with regard to its household electricity sector to both OECD and Non-OECD nations and similarities and differences are discussed. Further, by using a recently developed econometric technique - the bounds testing procedure to cointegration within an ARDL framework, both the long and short-run determinants of residential electricity consumption in South Africa are explored. The obtained results point out that both in the long and short term the level of disposable income and the undergoing urbanization processes have had an important impact on household electricity consumption patterns. In addition, testing the stability of the obtained parameters, the model proves its reliability.
Keywords: Electricity consumption; residential sector; South Africa; economic development; bounds testing; ARDL